1996
DOI: 10.1111/j.1440-1630.1996.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Students' perspective of fieldwork: Process, purpose and relationship to coursework

Abstract: This article describes the results of a naturalistic study of four student occupational therapists' early fieldwork experiences. Data from interviews, participant‐observation and students' daily journals were used to identify students' perspectives on the process and purposes of fieldwork. In addition, the relationship of fieldwork to coursework was explored. Students viewed fieldwork as consisting of phases with certain constants that were present in every placement. The main purposes of fieldwork were seen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fieldwork education had been described as a central component of the occupational therapy educational experience as it integrates knowledge, professional reasoning and behaviours in practice, and aims to develop skills and attitudes to the level of competence required of a qualified therapist (Bonello, 2001; Cook & Cusick, 1998). Tompson and Ryan (1996) found that the process of learning in fieldwork differed from coursework learning with fieldwork learning, allowing trial and error, practice of techniques, direct observation of clients, and motivation stemming from reactions of clients. Providing students with varied and plentiful fieldwork experiences that are ‘interspersed between and integrated with academic components of the curriculum’ (Tompson & Ryan, p. 102) provides an opportunity to be prepared for numerous practice settings upon entering the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Fieldwork education had been described as a central component of the occupational therapy educational experience as it integrates knowledge, professional reasoning and behaviours in practice, and aims to develop skills and attitudes to the level of competence required of a qualified therapist (Bonello, 2001; Cook & Cusick, 1998). Tompson and Ryan (1996) found that the process of learning in fieldwork differed from coursework learning with fieldwork learning, allowing trial and error, practice of techniques, direct observation of clients, and motivation stemming from reactions of clients. Providing students with varied and plentiful fieldwork experiences that are ‘interspersed between and integrated with academic components of the curriculum’ (Tompson & Ryan, p. 102) provides an opportunity to be prepared for numerous practice settings upon entering the workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Fieldwork placements are an integral component of occupational therapy curricula as they enable students to integrate academic knowledge with clinical skills in various practice settings (Bonello, 2001). Fieldwork placements have also been found to play a significant role in preparing students for clinical practice (Aiken, Menaker, & Barsky, 2001; American Occupational Therapy Association, 2009; Bonello, 2001; Tompson & Ryan, 1996) and in shaping their practice preferences (Crowe & Mackenzie, 2002; Hulse, Cash, & Simons, 2000). Researchers have found that international fieldwork placements (IFPs) foster the development of occupational therapy students in various ways, including increased confidence as a professional, enhanced ability to apply theory to practice, and improved clinical skills (Aiken et al, 2001).…”
mentioning
confidence: 99%
“…At the present moment, there appears to be a gap in information about the experience of the assessment of competence from the students' perspective. Sometimes it is referred to in studies exploring students' perspective of the fi eldwork experience in general (Alexander, 1996;Heath, 1996;Martin, 1996;Thompson and Ryan, 1996;Hummell, 1997). Fieldwork itself is highly valued by students (Mitchell and Kampfe, 1990;Seale, Chapman and Davey, 2000) and still forms approximately one third of most courses…”
Section: The Student Experience Of Assessmentmentioning
confidence: 99%
“…Firstly, the environment itself is not constant and therefore learning opportunities and priorities will necessarily vary (Meyers, 1989;Jacobs, 1992) and each new environment can be perceived initially as threatening (Burrows, 1989). Also having learned the 'ideal' from coursework, the realities of the actual fi eldwork setting could be disappointing and limiting to the student (Thompson and Ryan, 1996).…”
Section: Factors Which Infl Uence Fi Eldwork Assessmentmentioning
confidence: 99%